Agriculture, Diversification, and Gender in Rural Africa Longitudinal Perspectives from Six Countries - Andersson Djurfeldt, Agnes; Cuthbert Isinika, Aida; Mawunyo Dzanku, Fred (Oxford University Press, 2018)
This book contributes to the understanding of smallholder agriculture in sub-Saharan Africa through addressing the dynamics of intensification and diversification within and outside agriculture, in contexts where women have much poorer access to agrarian resources than men. It uses a longitudinal cross-country comparative approach, relying on the Afrint dataset-unique household-level longitudinal data for six African countries collected over the period 2002-2013/15. The book first descriptively summarizes findings from the third wave of the dataset. The book nuances the current dominance of structural transformation narratives of agricultural change by adding insights from gender and village-level studies of agrarian change. It argues that placing agrarian change within broader livelihood dynamics outside agriculture, highlighting country- and region-specific contexts is an important analytical adaptation to the empirical realities of rural Africa. From the policy perspective, this book provides suggestions for more inclusive rural development policies, outlining the weaknesses of present policies illustrated by the currently gendered inequalities in access to agrarian resources. The book also provides country-specific insights from Ghana, Kenya, Malawi, Tanzania, and Zambia.